HIC and SSC of Carbon Steel in High Partial Pressure CO2 Environments with Elevated H2S - Abas Ahmad Zaki; Nor Azmi Mohammed; Suhor Muhammad Firdaus; Rusli Ahmad Mustaza Ahmad; Ismail Mokhtar Che (E3S Web of Conferences, 2021)
The Hydrogen Induced Cracking (HIC) and Sulfide Stress Cracking (SSC) behaviours of sour service and non-sour service carbon steel API 5L X65 were investigated under high pressure carbon dioxide environments, containing elevated amount of hydrogen sulphide (H2S); the test environments simulated offshore pipelines transporting full-well streams in high carbon dioxide (CO2) environments with elevated H2S concentrations. It was systematically studied under standard NACE condition and high pressure carbon dioxide field condition with variation in other key parameters (temperature, pressure and hydrogen sulfide concentration). The HIC and SSC were tested using a High Pressure and High Temperature (HPHT) Autoclave. The surface cracking morphology was analysed using Scanning Electron Microscopy (SEM), Ultrasonic Technique (UT) and Magnetic Particle (MP). The results showed that no cracks were detected in NACE standard and field-condition SSC tests for both sour service and non-sour services carbon steel. In HIC test, crack was detected on non-sour service carbon steel in NACE standard test while no crack was detected on field condition-based tests for both types of carbon steel.